A radiographic analysis of the location of the mental foramen - Abdalmalik O. Ghandourah; Mohd. B. Badaoud; Anmar Dahlawi; Abdullah Alghamdi; Faisal Alhazmi; Shahinaz N. Sembawa; Abrar K. Demyati (Elsevier, 2023)
Background: Accurate knowledge and identification of anatomical landmarks on radiographic imaging are essential when preparing for any invasive procedure. The mental foramen has been the subject of many publications because of its significance as the origin point of the mental nerve and its proximity to the lower premolar area. The aim of this study was to assess the horizontal location of the mental foramen (MF) in the samples collected from the Faculty of Dental Medicine at Umm Al-Qura University, Mecca, Saudi Arabia. This included comparing genders, ages, and bilateral symmetry. In addition, the study aimed to assess inter-rater reliability in locating the mental foramen on a digital panoramic radiograph (OPG). Methods: A total of 334 digital panoramic radiographs were chosen for retrospective analysis from a total of 2,199 images taken from the Umm Al-Qura University, Faculty of Dental Medicine, teaching hospital database. The locations were scored independently by four examiners. The area was divided into six zones, determined by drawing straight lines along the long axis of the premolars and contact areas. A scoring index of 1-6 was utilized to describe the location in relation to the premolars. Analysis was carried out using chi-square and descriptive statistics. The inter-rater reliability was calculated using Fleiss' Kappa to determine observer agreement. Results: The ages of the patients ranged from 13 to 76 years, with a mean of 29.66. There was no significant difference related to gender, but there was a significant difference related to age. The most frequent location was zone 4, 47.6% on the left side and 51.5% on the right, followed by zone 5, 18.6% on the left side and 16.2% on the right, and zone 3, 15.3% on both the right and the left side. The location was symmetrical in 64.7% of the cases and asymmetrical in 35.3%. The inter-rater reliability among the examiners was fair. Conclusions: The findings of this study indicate that the MF's location was more closely related to the mandibular second premolar than the first premolar. Furthermore, bilateral symmetry was found in 65% of the sample. There was no statistical significance observed in differences between the genders. Both newly graduated and experienced dentists could identify the location of the MF from the radiograph using the MF's location in relation to the six zones.